Imroving metods of the main pests of rice (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The subject of the study is rice. The purpose of the research was to determine the species composition of pests living in the agrobiocenosis of rice, to improve the overall protection system using modern means and methods of combating them based on studying the dynamics of their development, the level of harmfulness of rice. The objectives of the study were to determine the species composition of harmful pests in the phases of rice germination and development, to determine the dynamics of the development of rice pests, and to analyze natural entomophages in rice fields. The scientific significance of the research results lies in the fact that the main types of rice pests have been studied, which need to improve the methods of their distribution, damage and (agrotechnical, chemical) control. The type and significance of entomophages have been studied.
Keywords: diseases, pests, rice, quality, ecological purity, phases, yield, agrobiocenosis, ecosystem, species